Contribution of non-timber forest products (ntfps) utilization to the well-being of women: evidence from Nigeria (2021)
This paper assessed the contribution of NTFPs to the well-being of women living in Ewekoro Local Government Area of Ogun State, Nigeria. Logistic regression and Ordered Logistic regression models were used to assess the contribution of NTFPs to the well-being of 120 women in the study area. The mean age, monthly household income, distance of homestead to forest and homestead to the nearest market were 47 years, $144.4, 2.0km and 1.8km respectively while 70.5% of the women used NTFPs as food. The housing dimension had the highest index of 0.537 while the overall index of 0.491 indicates a moderate level of well-being for respondents. NTFPs utilization significantly increased with household income and primary occupation but decreased with increasing age, level of education, distance from homestead to forests, distance to the nearest market and access to credit. Women’s well-being increased with utilization of NFTPs, being married, distance from homestead to the nearest market and access to credit but decreased with the distance of homestead to the forest, association membership and income. It is recommended that agricultural advisory and extension services in terms of NTFPs collection and utilization be provided; unconditional cash transfers and other consumption smoothening aids should be provided; necessary road networks should be rehabilitated or constructed, this will enhance NTFPs utilization; credit access should be provided for rural women, and rural women should be mobilized to form and/or join associations. Given that, NTFPs utilization contributes to the well-being of women, policies and programs that will enhance women’s utilization of NTFPs should be put in place.